Cost-utility and cost-benefit analysis of pediatric PCV programs in Egypt. Issue 6 (30th November 2022) - Sevilla, JP; Burnes, Daria; El Saie, Rehab Zakaria; Haridy, Hammam; Wasserman, Matt; Pugh, Sarah; Perdrizet, Johnna; Bloom, David
ABSTRACT: New vaccine introductions (NVIs) raise issues of value for money (VfM) for self-financing middle-income countries like Egypt. We evaluate a pediatric pneumococcal conjugate vaccine (PCV) NVI in Egypt from health payer and societal perspectives, using cost-utility and cost-benefit analysis (CUA, CBA). We evaluate vaccinating 100 successive birth cohorts with the 13-valent PCV ("PCV13") and the 10-valent PCV ("PCV10") relative to no vaccination and each other. We quantify health effects with a disease incidence projection model and a multiple-cohort static disease model. Our CBA uses a health-augmented lifecycle model to generate willingness-to-pay for health gains from which we calculate rates of return (RoR). We obtain parameters from the published literature. We perform deterministic and probabilistic sensitivity analysis. Our base-case CUA finds incremental cost-effectiveness ratios (ICERs) for PCV13 and PCV10 relative to no program of 926 (95% confidence interval 512–1, 735) and 1, 984 (1, 186-3, 805) per quality-adjusted life year (QALY), respectively; and for PCV13 relative to PCV10 of 174 (88-331) per QALY. Our base-case CBA finds RoRs to PCV13 and PCV10 relative to no program of 488% (188–993%) and 164% (33–336%), respectively, and to PCV13 relative to PCV10 of 3109% (1410–6602%). Both CUA and CBA find PCV13 to be good VfM relative to PCV10.